Frauenlexikon: Traditionen, Fakten, Perspektiven - Lissner, Anneliese; Dunde, Siegfried Rudolf (Reihe Frauenforum, 1988)
Anneliese Lissner, Rita Süssmuth, Karin Walter (Hrsg.): "Frauenlexikon - Traditionen, Fakten, Perspektiven". Herder Verlag, Freiburg, Basel, Wien 1988. 1246 Seiten, geb., 58,- DM